Determination of Sex of Sacrum in Adult Bangladeshi People by Morphometric Study (IAHS Medical Journal, 2022)
Background: Sex determination from bones is of vital importance in anthropological studies and medico-legal cases. Sacrum is one of the bones, which exhibits sex differences. Literature available on this bone shows that not much study has been done in the population of Bangladesh. In the present study, an attempt has been made to test the validity of the parameters that are useful in differentiating male and female sacra. The present study was conducted to see the sexual dimorphism and morphometry of sacrum in adult Bangladeshi people. This study will be useful for anatomists, experts in forensic medicine and physical anthropologist for more accurate sexing of sacra.Materials and methods: Descriptive, cross-sectional study was conducted in the Department of Anatomy, Chittagong Medical College, Chattogram on 100 dry human sacra of known (Male-46, female-56) sex during January 2014 to December 2014. The measurements included for the study were maximum length, maximum width, mid ventral curved length, transverse diameter of first sacral vertebra, length of ala, maximum length of auricular surface and indices like curvature index, sacral index, corporo-basal index, alar index, index of body of S1, auricular index were calculated and statistically analyzed.Results: In the present study the male sacrum showed significantly higher values for ventral straight length, ventral curved length, transverse diameter of S1 and antero-posterior diameter of S1 than the female sacrum, while the female sacral index showed higher value compared with the values of male.Conclusion: From the above parameters and indices in the present study revealed demarking points for each have statistical significant role in determining the male and female sacrum.IAHS Medical Journal Vol 4(1), June 2021; 2-4